Determinants of graduate starting salary: a case study / Nora Mohd Basir ... [et al.] - Mohd Basir, Nora; Zubairi, Yong Zulina; Jani, Rohana; Abdul Wahab, Diana (Universiti Teknologi MARA, Negeri Sembilan, 2022)
In the era of growing technological convergence, the number of graduates produced by public and private universities is seen to be increasing. However, not all graduates are fortunate enough to secure a job or succeed in getting a job that matches with their qualification (Steed, 2018). In May 2019, Malaysia recorded unemployment rate of 3.3%, a marginal decrease compared to 3.4% that was recorded in previous month (Department of Statistics Malaysia, 2019). Nevertheless, this unemployment rate does not in depth information in particular the breakdown the unemployment by levels of education. When graduates are offered a job, one of the important factors they will take into account is the salary offered. For graduates who are offered jobs in a giant or multinational company, it is always presumed that the graduate will earn a high starting salary. However, no study can confirm this assumption. Salary in general known as a fixed payment that paid periodically for a person that engaged with work or service. This payment however scattered differently within each fresh graduate even though they are from the same background of the study. There is no clear evidence that well-established company will provide higher starting salary compared to less known company.